Cytotoxic T-Cell-Mediated Response against Yersinia pseudotuberculosis in HLA-B27 Transgenic Rat - Falgarone, Géraldine (American Society for Microbiology, 1999)
Yersinia-induced reactive arthritis is highly associated with HLA-B27, the role of which in defense against the triggering bacteria remains unclear. The aim of this study was to examine the capacity of rats transgenic for HLA-B27 to mount a cytotoxic T-lymphocyte (CTL) response against Y. pseudotuberculosis and to determine the influence of the HLA-B27 transgene on this response. Rats transgenic for HLA-B*2705 and human β(2)-microglobulin of the 21-4L line, which do not spontaneously develop disease, and nontransgenic syngeneic Lewis (LEW) rats were infected with Y. pseudotuberculosis. Lymph node cells were restimulated in vitro, and the presence of for Y. pseudotuberculosis-specific CTLs against infected targets was determined. Infection of 21-4L rats triggered a CD8(+) T cell-mediated cytotoxic response specific for Y. pseudotuberculosis. Analysis of this response demonstrated restriction by an endogenous major histocompatibility complex molecule. However, no restriction by HLA-B27 was detected. In addition, kinetics studies revealed a weaker anti-Yersinia CTL response in 21-4L rats than in nontransgenic LEW rats, and the level of cytotoxicity against 21-4L lymphoblast targets sensitized with Y. pseudotuberculosis was lower than that against nontransgenic LEW targets. We conclude that HLA-B27 transgenic rats mount a CTL response against Y. pseudotuberculosis that is not restricted by HLA-B27. Yet, HLA-B27 exerts a negative effect on the level of this response, which could contribute to impaired defense against Yersinia.